PENGARUH PROBIOTIK PADA RESPON IMUN - Djunaedi, Djoni (Fakultas Kedokteran Universitas Brawijaya, 2007)
Probiotics (â€œfor lifeâ€) is a live microbial feed supplement or defined as mono- or mixed cultures of live microorganismsÂ which when administered in adequate amounts confer Â a health benefit to the host by improving its microbial balance.Â Common descriptives for probiotics include â€œfriendlyâ€, â€œbeneficialâ€ or â€œhealthyâ€ bacteria. Â Under natural conditions aÂ protective gut microflora develops and there is no Â need for probiotics supplement, but under rather un-natural conditionsÂ such like intestinal infections, post antibiotic treatment syndromes, pseudomembranous colitis, the probiotics preparationsÂ are needed. The beneficial effects of probiotics inthe host are promotion of the gut maturation and integrity, antagonismsÂ against pathogens and immune modulation. Beyond those, the microflora seems to play a significant rolein diet inducedÂ superinflammation, mucosal immune system, neuroendocrine regulation, immunoglobulin production, macrophages factorÂ restoration, apoptosis stimulation, lymphocyte function modulation, cytokine release, mucin production, intestinal immuneÂ homeostasis and inflammation prevention. However, many studies proved that probiotics have â€œupregulation and down-regulationâ€ effects on immune system of the host.